If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m/12+9=11
We move all terms to the left:
m/12+9-(11)=0
We add all the numbers together, and all the variables
m/12-2=0
We multiply all the terms by the denominator
m-2*12=0
We add all the numbers together, and all the variables
m-24=0
We move all terms containing m to the left, all other terms to the right
m=24
| (x+5)^2-17=32 | | 4+c= -5 | | 6x+4=8+4x | | 12=4x | | 8x+3+2x=5(2x+3) | | Y=-7x+350 | | 180(14-2)=x | | X+4/2=x-9 | | 86+48+x=134 | | (2.5-2.5)=x+3-5 | | 2x+2/4=-3 | | 8c+6=10c | | 3n+10=3()+10 | | 31 (x+4)=20x=48 | | p/2+20=14 | | F(x)=8A^9 | | 7x^2-6=29 | | 3x/4+10=-25 | | 5n+34=2n+14 | | -12=-4+s | | x-(-2)=30 | | 2/x+5=-12/x-2 | | 2(34+12)=5b | | 49/x=-6 | | 2x-4x+12=-2x+12 | | 5n+23+3n+29=180 | | 3x-30=42 | | 13=3/4n+1 | | p/4-5=0 | | 3(6+5y=2(-5+4y) | | 22=-2h | | 2x-2/2=-2 |